Conceptual Model of a Dashboard for Monitoring Microservices - Prayudi Utomo; Falahah Falahah (EAI Endorsed Transactions on Cloud Systems, 2020)
The popularity of microservices architecture in building software for the distributed environment leave some problem, such as configuration, orchestration, and monitoring. Some technology and software had been built and implemented, but it has certain constraints for implementation such as its complexity in configuration and needs many components for running. The aim of this research is to propose the conceptual model of a dashboard for monitoring. The model consists of components, the interaction between components, and the requirements for each component. We used Model Driven Architecture (MDA) for describing the model and building the visual prototype based on the model. We used a black-box approach and monitored the microservices through its endpoint. We also propose a simple algorithm for determining endpoint status. We argue that our model will provide flexibility on implementation and can be implemented in a small or medium microservices environment.